Pemberian Izin Usaha Toko Modern Alfamart Dan Indomaret Oleh Pemerintah Kota Ambon - Samangun, Warnesy Atayen; Pattinasarany, Yohanes; Nirahua, Garciano (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The problem studied in this research is about the granting of business licenses for modern stores alfamart and indomaret by the Ambon City Government based on the Presidential Regulation and the Regulation of the Minister of Trade which requires Regional Governments to establish their respective Regional Regulations related to the granting of business licenses for the construction of modern stores that have not been implemented by the Ambon City Government and the legal consequences of the negligence of the Regional Government.Purposes of the Research: Methods of the Research: The method used in analyzing and discussing the problem is normative research method. The Ambon City Government until now still has not established a Regional Regulation to regulate the granting of business licenses for modern alfamart and indomaret stores, this has resulted in the construction of modern alfamart and indomaret stores which are built in close proximity so that they can cause unfair competition between modern stores and people's markets / traditional shopsResults / Findings / Novelty of the Research: The results showed that the Ambon city government, before the enactment of the Job Creation Law, always issued business licenses for the establishment of modern alfamart and indomaret stores based only on the Presidential Regulation and Permendag, but did not ignore its obligation to establish its Regional Regulations to regulate the granting of business licenses for modern alfamart and indomaret stores in the city of Ambon itself, resulting in a lot of unhealthy competition between small shop entrepreneurs or people's markets with traditional shops.